Tunable Quantum Anomalous Hall Gap in Compressed Graphene/CrI3 van der Waals Heterostructures - Ren, Jun‐Tong; Feng, Yuan; Ke, Sha‐Sha; Lü, Hai‐Feng (Advanced Physics Research, 2025)
Two‐dimensional magnetic heterostructures have attracted special attention due to their potential applications in fundamental physics and spintronics. Here, the magnetic and electronic properties of the van der Waals heterostructure formed by graphene and CrI3 is investigated. The first‐principles calculations show that the spin‐polarized electron density of graphene sensitively depends on the charge transfer between graphene and CrI3, which can be modulated by applying an electric field. However, the spin‐polarized density exhibits a non‐monotonic change with electric field due to the unstable charge distribution between graphene and CrI3. When the interface distance is compressed by 1.1 Å, the enhanced interaction between graphene and CrI3 stabilizes the charge distribution. As a result, the quantum anomalous Hall gap increases from 6 to 22 meV with an external electric field in the compressed heterostructure. In addition, halogen ligands play an important role in the interaction between Cr atoms and graphene and can regulate the range of spin‐polarized density. In the van der Waals heterostructures Gr/CrI3, the spin‐polarized density of graphene exhibits a non‐monotonic change with electric field due to the unstable charge distribution. When the interface distance is compressed, the enhanced interaction between graphene and CrI3 stabilizes the charge distribution, and the quantum anomalous Hall gap can be tuned from 6 to 22 meV.